ANALYSIS OF THE DRAMA MANUFACTURE BEN GO TUN BY SAINI KM USING A SOCIOLOGICAL APPROACH METHOD - Shofi Al Zahra; Rifa Fauziah Salma; Jein Fitria Sriwulan Pitaloka; Lisa Herlina; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research uses a descriptive qualitative approach with a library study model. The data collection technique used in this research is based on data analysis in the Ben Go Tun drama script. This research was carried out by directly examining the Ben Go Tun drama script by taking primary and secondary data. From the research results, there are three main discussions, namely conflict, criticism and moral messages. Of these three discussions, one of them is conflict. Several conflicts told in the Ben Go Tun drama script are analyzed in dialogue and juxtaposed with the realities of life. Then there is social criticism which is analyzed as an outline of the background of the drama script Ben Go Tun. And finally there is a moral message, the author analyzes every criticism and conflict to retrieve data related to the resulting moral message. This research draws from several appropriate theories and is linked to the drama script Ben Go Tun which has been analyzed using a sociological approach.